1999
DOI: 10.1002/(sici)1521-3773(19990712)38:13/14<1974::aid-anie1974>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Beside Ionic: Crystal Structures of a 1/1 and a 1/4 Adduct of Pyridine and Formic Acid

Abstract: Of two low‐melting binary adducts obtained with the same universal organic acid and base components, one contains these as the neutral molecules, the other, however, in a deprotonated and a protonated form as ions. Reports on analogous results for further Brønsted acid/base systems are rare. The complex anion, new in a crystal structure, is assembled by strong hydrogen bonds O−H⋅⋅⋅O (see formula).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The exact ionization state is difficult to predict and it was commented that the molecular environment in each crystal structure is unique and can affect the amount of proton transfer. For example, pyridine and formic acid form a co-crystal in 1:1 ratio, while it forms a salt in 1:4 ratio [11]. Recently, A.J.…”
Section: Introductionmentioning
confidence: 99%
“…The exact ionization state is difficult to predict and it was commented that the molecular environment in each crystal structure is unique and can affect the amount of proton transfer. For example, pyridine and formic acid form a co-crystal in 1:1 ratio, while it forms a salt in 1:4 ratio [11]. Recently, A.J.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure , the optimized unit cells of 1:1 cocrystal and 4:1 salt are shown along with their asymmetric units. The initial structures are retrieved from the Crystallographic Information Files (CIFs) of the experimental structures . In both cases, the lattice parameters get contracted by only ∼3% upon optimization with respect to the experimental crystal structure, indicating robustness of our computations.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, however, on further increase in the ratio of formic acid to pyridine to 4:1, there is a sharp O–H···N → O – ···H–N + proton transition which leads to formation of the salt phase. It consists of one pyridinium cation, one formate anion along with three additional neutral formic acid molecules. , Previously, in the context of inorganic acid–base reactions between NH 3 and HX (X = F, Cl, Br, NO 3 , HCO 3 , and HSO 4 ), we have also shown that the proton transfer from hydrogen bonded complex (NH 3 ···HX) to ionic salt (NH 4 + X – ) is facilitated via cooperativity by increasing their stoichiometric ratio . Hence, while the 2:1 mixture of NH 3 and H 2 SO 4 is a H-bonded complex (NH 3 ···H 2 SO 4 ···NH 3 , cocrystal-like), its higher analogue (4:2 mixture) is a salt, (NH 4 ) 2 SO 4 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation